Individual Creativity in Digital Transformation Enterprises: Knowledge and Ability, Which Is More Important? - Jiang, Daokui; Chen, Zhuo; Liu, Teng; Zhu, Honghong; Wang, Su; Chen, Qian (Frontiers in Psychology, 2022)
Digital technological innovation is reshaping the pattern of industrial development. Due to the shortage of digital talents and the frequent mobility of these people, the competition for talents will be very fierce for organizations to realize digital transformation. The digitization transformation of China's service industry is far ahead of that of industry and agriculture. It is of great significance to study the organizational management and talent management of service enterprises to reduce the negative impact of insufficient talent reserve and meet the needs of digital development. Based on 378 valid questionnaires from China's service industry, this paper applied polynomial regression and a response surface model to analyze the impact of two kinds of person-environment fit on work engagement and individual creativity. The results show that (1) under the combination of high morality and high talent, work engagement and individual creativity are the highest; (2) individual creativity is stronger under the condition of high morality and low talent than under low morality and high talent; and (3) work engagement mediates the influence of morality and talent on individual creativity. The research reveals the internal mechanism by which morality and talent cooperatively promote individual creativity, which provides theoretical guidance for management practice of service firms to improve individual creativity in the process of digital transformation.